Perancangan Sistem Informasi Monitoring dan Pelaporan Kinerja Aparatur Sipil Negara Berbasis Web dan Android - Ridwan Setiawan; Dede Kurniadi; Yayat Supriatna (Institut Teknologi Garut, 2023)
The large number of activities and the number of State Civil Apparatus (ASN) that must be reported makes it difficult for the government to evaluate the performance of workers. The purpose of this study was to design an information system for monitoring and reporting ASN performance in Leles District using the Scrum methodology where this technique can be used for overall system development, partial system development, and internal/customer projects. With the results of the system in the form of designing web-based and Android applications. The modeling uses the unified modeling language (UML), namely use cases, class diagrams, interfaces and prototypes. This research is only limited to the performance report of the state civil apparatus until the validation process by the supervisor until the report is complete. Using this information and monitoring system can reduce the time it takes to send physical evidence of ASN performance to supervisors and reduce the possibility of errors or lack of reporting evidence.